FLEXURAL WAVE ENERGY TRANSFORMATION ON THE STEPS AT VARIOUS PARAMETERS OF THE CONTACTING MEDIA - Городецька, Н. С.; Неділько, О. О. (Science-based technologies, 2015)
The diffraction of the Rayleigh-Lamb wave on a vertical boundary of waveguide formed by a strong contact of two half-strips is calculated for case of their different widths and different mechanical properties. It is shown that there are two frequency range, in which are observed increasing energy of the reflected field. The first maximum of energy of reflected field is observed near the locking frequency for the second propagating wave. It is caused by the existing of the second propagation wave. The amount of energy in the reflected field at the frequency of the maximum decreases with an increase in the width of a narrow half-strip . If the second propagating wave appears in transmitting field earlier than in reflected one, the maximum of energy of reflected field is observed at the critical frequency of this wave. If the second propagating wave appears in reflected field earlier than in transmitting field than maximum of energy of reflected field is detected at the frequency (higher critical) for the second propagating reflected wave. Second peak exists in the higher frequency region and causes considerable excitement evanescent waves .